Silver Lining - Ručka, Svatopluk (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Silver Lining vzniká na základě interdisciplinárního zkoumání dvou oborů designu — módního a grafického. Na tyto dvě disciplíny je nahlíženo z praktického hlediska, v němž jsou zkoumány postupy práce obou designerských sfér, jejich vzájemný vztah, možné průsečíky a (reálné i hypotetické) syntézy. Potenciál takové syntézy je zkoumán vizuálním jazykem grafického designu a módní tvorby pomocí současné digitalizované pletací technologie, s níž bakalářská práce nakládá.

Silver Lining is created on the basis of the interdisciplinary research of the two disciplines of design, i.e., fashion and graphic designs. These two branches of design are viewed from the practical point of view, in which the work procedures of both the design branches, their mutual relationship, possible intersections, and real and hypothetical syntheses are examined. The potential of such a synthesis is studied by the visual language of the graphic design and fashion production using contemporary digitalized knitting technology which is applied in the bachelor’s thesis.
Silver Lining
Keywords: móda; oděv; textil; design; spolupráce; pletenina; technologie; inovace; 3D; praxe; funkce.; fashion; clothing; textile; design; collaboration; knitwear; technology; innovation; 3D; practice; function.